"The Impact of Operational Risks on the Preferences of Syrian Private Commercial Banks" - دنوره نور; نهاد نادر; رامي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2023)
his study aimed study the impact of operational risks on the preferences of Syrian private commercial banks and their relationship with them. The needed data was collected from the financial statements, and official statistics of the banks under study, which are eleven banks that represented the study sample during the period (2011-2021). For the purposes of analysis, the Pearson correlation coefficient and the simple linear regression model were used to study the relationship of operational risks with preferences for liquidity, profitability, and banking safety and their impact on them. The results of the study showed that, there is a strong direct correlation with statistical significance between operational risks and both safety preference and liquidity preference (total liquid and semi-liquid assets/ total deposits; total liquid assets/ total deposits) in Syrian private commercial banks, and it also showed a weak direct correlation with statistical significance between operational risks and profitability preference (Return On Assets; Return On Equity) in Syrian private commercial banks, while the study results showed that there is no statistically significant correlation between operational risks and liquidity preference (ratio of total liquid assets/ total assets) in Syrian private commercial banks. The research recommended the need for the Syrian private commercial banks to publish the details related to operational risks clearly, and to maintain high and good levels of preferences (Safety, Profitability, Liquidity) in the Syrian private commercial banks due to their important role in raising the level of performance.